2017
DOI: 10.17509/jpm.v2i2.8105
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja Mengajar Guru Sebagai Faktor Determinan Prestasi Belajar Siswa

Abstract: The problem in this research is not optimal student achievement. It is characterized by the acquisition of learning outcomes of student who have not reached the Minimum Completeness Criteria in school. This study aims to determine the effect of performance of teaching teachers on student achievement. The method used in this research was survey method. Data collection techniques used question model on scale of 1-5 form with rating scale. Respondents were 53 students of class X of Office Administration Vocationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 8 publications
(9 reference statements)
0
15
0
10
Order By: Relevance
“…The results of learning process in this study shows that the teacher's role is very large in efforts to make students achieve maximum learning outcomes, or in other words learning management has an effect on teacher performance [12], and teacher teaching performance has a significant in learning achievement [13]. Through the learning outcomes obtained in this study in the form of essay writing skills scores indicated that the application of the scaffolding learning model provides a significant increase in learning outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…The results of learning process in this study shows that the teacher's role is very large in efforts to make students achieve maximum learning outcomes, or in other words learning management has an effect on teacher performance [12], and teacher teaching performance has a significant in learning achievement [13]. Through the learning outcomes obtained in this study in the form of essay writing skills scores indicated that the application of the scaffolding learning model provides a significant increase in learning outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…Temuan keempat, Kinerja guru meningkat dalam melaksanakan tindak lanjut hasil penilaian prestasi belajar peserta didik. Prestasi belajar siswa merupakan hasil belajar siswa yang merupakan tolak ukur keberhasilan guru dalam belajar (Rohmah & Marimin, 2015;Yulianingsih & Sobandi, 2017). Langkah-langkah yang dapat meningkatkan kinerja guru dalam supervisi edukatif kolaboratif adalah: (1) Peneliti dan guru bersama-sama membuat program tindak lanjut hasil penilaian, (2) Peneliti memberi contoh pelaksanaan tindak lanjut, yang akhirnya dilanjutkan oleh guru dalam pelaksanaan yang sebenarnya, (3) Peneliti mengajak diskusi pada guru yang telah membuat, melaksanakan, dan menganalis program tindak lanjut.…”
Section: Resultsunclassified
“…This is caused by several things including external factors that are very influential namely the teacher [7]. In the learning process that applies the number head together learning model, the teacher has not managed the class maximally, so the planned learning process has no power created in the discussion process [8]. On the other hand, students also as part of external factors supporting the achievement of optimal learning outcomes have not provided synergy in the application of the learning model.…”
Section: Discussionmentioning
confidence: 99%